A Comparison of Digestion Methods on Evaluation Analytical Performance Heavy Metals Contamination in Soil and Vegetables: A Case Study in Nam Suay Subdistrict, Mueang Loei District, Loei Province - Wongpriaw, Napatsorn; Thammasom, Thitinan; Puttanu, Bussabavadee; Pongsuk, Pattranuch; Phramueangkhong, Suphat (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2024)
The study aims to analyze the content of three heavy metals in soils and Brassica rapa L. Six digestion methods, including method-1; prepared the samples; digestion with nitric acid, method-2; digestion with nitric acid in overnight, method-3; digestion with nitric acid and hydrogen peroxide, method-4; digestion with nitric acid and perchloric acid, method-5; digestion with sulfuric acid and method-6; dry ash. Heavy metal contents such as cadmium (Cd), lead (Pb), and arsenic (As) were analyzed using graphite furnace atomic absorption spectrostometry (GF-AAS). The results revealed that the concentration ranges of cadmium (Cd), lead (Pb), and arsenic (As) in B. rapa L. were ND-0.03±0.02, 0.07±0.02-0.12±0.04, and ND-0.02±0.03 milligram per kilogram (mg/kg), respectively. The soil samples found heavy metal contents in the ranges of ND-0.15±0.03, 18.75±0.36-20.21±0.15, and ND-2.04±0.03 mg/kg, respectively. The evaluation of six digestion methods of B. rapa L. on the analytical performance of heavy metals, including cadmium, lead, and arsenic, showed a linearity range of r2 ≥ 0.995. The comparison of six digestion methods found the best preparation sample in removing the matrix, and the efficiency of analysis of heavy metal showed in method-6 as dry ash at 480 °C for 4 hours. The recovery percentages for cadmium, lead, and arsenic were found in the 99.77-90.17% range. Limit of detection (LOD) and quantitation (LOQ) were 0.0027-0.0519 and 0.0090-0.0519. In addition, the sample preparation of method-1; prepared the samples; digestion with nitric acid and method-3; digestion with nitric acid and hydrogen peroxide were also acceptable. The substances were inexpensive, easy, and fast to analyze. The recovery percentage, LOD, and LOQ were 85.75-80.12, 0.0497-0.0029, and 0.1656-0.0097, respectively. The transfer factor of heavy metal from soil to vegetables has been found to have decreased. The contamination of heavy metals was less than that of the World Health Organization. This indicates that it is safe for consumption.